Towards Sustainable Development: Indonesia Project-Based Sukuk for Infrastructure - Dewi, Nila; Mulyati, Yati; Tantular, Yoga; Abdulhadi, Dudi; ., Islahuzzaman (International Journal of Engineering and Technology, 2018)
Indonesiaâ€™s economy the last few years has showed a good performance, although faced with the challenges of the global economy. However, the achievement of economic growth still has not been accompanied by equalization and adequate infrastructure. Infrastructure has an important role in supporting economic growth and thereby promotes to the reduction of economic disparity and poverty. Greater access of the poor to education and health services, water sanitation, employment, credit and markets produce is needed for creating sustainable and socially inclusive development. Recent innovation in project financing schemes to accelerate the provision of infrastructure is the implementation of sharia compliant financing. The issuance of Project Based Sukuk as an instrument for infrastructure financing has potential to enhance sustainable development. Thus, this study aims to determine the opportunities and challenges through descriptive analysis method. The result indicates that the challenges consist of investors aspects include: lack of understanding, averse to risk, market liquidity, and supporting aspects such as innovation and regulatory framework. Short term and long term strategies are applied including fundamental, technical, and roadmap strategy which are expected for the implementation of project-based sukuk in the future.Â